The Quality Testing of Rangkui River Water in Pangkalarang Area, Pangkalpinang City - Wiati, Irene Tresna; Erika Fitri Wardani (Journal of Civil Engineering and Planning (JCEP), 2025)
The availability of clean water is very important for improving public health. Clean water sources can come from the ground, rivers, dug wells, and so on. The Pangkalarang community also really needs clean water. Currently, they only use dug well water that does not meet health requirements. The quality of clean water in this area is affected by seawater intrusion that pollutes groundwater. Pangkalarang has a surface water source in the form of Rangkui River water whose quality must be known if it is to be used as clean water. So researchers consider it necessary to conduct laboratory tests on river water samples. The parameters tested were pH (5.83) so that the pH of the water is categorized as an acidic liquid because the pH value is less than 7), COD (the highest value is 39.8 mg/L while the standard value is 10 mg/L), BOD (the highest value is 4.52 mg/L while the standard value is 2 mg/L), heavy metal content Zn (value <0.0377 mg/L and while the standard value is 0.01 mg/L), and Eschericia Coli bacteria content (the highest value is 350 MPN/100 ml while the standard value is 0 MPN/100 ml) according to PP Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. Based on laboratory tests, Rangkui River water does not meet health requirements. Therefore, researchers do not recommend the river water as a source of clean water.